Teacher's Effort In Improving Early Children's Language Development - Wilma Rahmah Hidayati; Delfi Eliza; Saiful Anwar (Universitas Muhammadiyah Ponorogo, 2022)
This study aims to determine the efforts that can be made to improve early childhood language development in schools. Derived from the results of previous studies, it is known that there is still a lack of language development in children at an early age. This can be influenced by many factors, including boring learning in school, stuck learning methods, and the lack of creativity of teachers in creating an exciting learning environment. The research method used in this research is literature study research, where the system data retrieval comes from books or journals analyzed based on existing problems. The results of the research show that in improving children's language development, stimulation is needed. In early childhood learning, the role of the teacher is vital because the teacher will become a motivator, facilitator and mediator. There are many ways that teachers can improve children's language development so that learning becomes fun and enjoyable for children, such as using the play method, namely using serial image media, picture media in a sandbox, and storytelling methods. From the results of this study, it is concluded that the development of children's language skills can improve.